Update on inflation of journal prices: medical journals, U.S. journals, and Brandon/Hill list journals. - Kronenfeld, M R (1989)
This paper examines the increases in prices for the last twenty years for the journals listed in the 1987 Brandon/Hill list and for the last twelve years for those on a list of medical and general periodicals published annually in Library Journal. This information is compared to the general U.S. inflation rate as measured by the Consumer Price Index. Despite the decline in the general rate of inflation, the buying power of libraries has continued to dwindle. Librarians need to use this information when justifying increased budget requests. They also need to interact more effectively with publishers to resolve this problem. The buying power of the dollar (as compared to the 1975 dollar) spent on the Brandon/Hill list journals is now 59% of that of a dollar spent in the general economy. This compares to 64% in 1983, when this research was last updated.